2006
DOI: 10.1073/pnas.0505723102
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Keap1/Nrf2 pathway for neuroprotection by electrophillic phase II inducers

Abstract: Electrophilic neurite outgrowth-promoting prostaglandin (NEPP) compounds protect neurons from oxidative insults. At least part of the neuroprotective action of NEPPs lies in induction of hemeoxygenase-1 (HO-1), which, along with other phase II enzymes, serve as a defense system against oxidative stress. Here, we found that, by using fluorescent tags and immunoprecipitation assays, NEPPs are taken up preferentially into neurons and bind in a thiol-dependent manner to Keap1, a negative regulator of the transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
236
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(241 citation statements)
references
References 17 publications
3
236
0
2
Order By: Relevance
“…Increasing evidence suggests that HO1 can be upregulated through the Nrf2/ARE-mediated pathway (Satoh et al, 2006;Zhao et al, 2006). We have shown that Nrf2, a key regulator of the HO1 gene, has an important role in protection against cerebral ischemic stroke (Shah et al, 2007).…”
Section: Introductionmentioning
confidence: 86%
“…Increasing evidence suggests that HO1 can be upregulated through the Nrf2/ARE-mediated pathway (Satoh et al, 2006;Zhao et al, 2006). We have shown that Nrf2, a key regulator of the HO1 gene, has an important role in protection against cerebral ischemic stroke (Shah et al, 2007).…”
Section: Introductionmentioning
confidence: 86%
“…Both events would lead to elevated levels of active Nrf2 and Nrf2 nuclear accumulation. Although the details of the molecular mechanisms of the Nrf2-mediated response to electrophile stress remain to be elucidated, it seems somewhat provocative to suggest that, at low concentration, acrolein may actually exert cytoprotective effects by inducing phase II enzymes via activation of Nrf2 [119].…”
Section: Acrolein As An Inducer Of the Keap1-nrf2-dependent Are/epre mentioning
confidence: 99%
“…[5][6][7][8][9] The accumulation of ROS in neurons results in lipid peroxidation, protein oxidation, DNA damage, and finally cell death. [5][6][7][8][9] Nowadays an active search for new cerebroprotectors is being carried out among compounds, that affect the compensatory shunt of ATP synthesis in conditions of cerebral ischemia, that modulate glutamate-and GABAergic systems, regulate activity of Ca-channels and system of nitrogen oxide, and also among antioxidants, neuropeptides, expression inhibitors of proinflammatory cytokines and antagonists of IL-1β-receptors. 2,10 Strong interrelation between disorder of energetic and plastic metabolism, their effect on course and prognosis of disease are often ignored while making treatment regimens; the main pathogenic treatment is deemed to be hemodynamic recovery.…”
Section: Introductionmentioning
confidence: 99%